Two-dimensional genome-scan identifies novel epistatic loci for essential hypertension - Tzenova Bell, J; Wallace, C; Dobson, R; Wiltshire, S; Mein, C; Pembroke, J; Brown, M; Clayton, D; Samani, N; Dominiczak, A; Webster, J; Lathrop, G; et al. (Oxford University Press, 2006)
It is well established that gene interactions influence common human diseases, but to date linkage studies have been constrained to searching for single genes across the genome. We applied a novel approach to uncover significant gene-gene interactions in a systematic two-dimensional (2D) genome-scan of essential hypertension. The study cohort comprised 2076 affected sib-pairs and 66 affected half-sib-pairs of the British Genetics of HyperTension study. Extensive simulations were used to establish significance thresholds in the context of 2D genome-scans. Our analyses found significant and suggestive evidence for loci on chromosomes 5, 9,11, 15, 16 and 19, which influence hypertension when gene-gene interactions are taken into account (5q13.1 and 11q22.1, two-locus lod score = 5.72; 5q13.1 and 19q12, two-locus lod score = 5.35; 9q22.3 and 15q12, two-locus lod score = 4.80; 16p12.3 and 16q23.1, two-locus lod score= 4.50). For each significant and suggestive pairwise interaction, the two-locus genetic model that best fitted the data was determined. Regions that were not detected using single-locus linkage analysis were identified in the 2D scan as contributing significant epistatic effects. This approach has discovered novel loci for hypertension and offers a unique potential to use existing data to uncover novel regions involved in complex human diseases.